The history and social foundations of American education - Davidson, Barry; Minnick, Charlotte (Journal of Interdisciplinary Studies in Education, 2012)
The History and Social Foundations of American Education is a well written, easy to read textbook outlining educational developments that formed the foundation of modern American schools, accompanied by helpful critical analysis and action activities listed at the conclusion of each chapter. A supporting bibliography cites current, classic, and historic references for reader follow-up.